Determinants of Fraud Risk in the Free Nutritious Meals Program: The Effects of Pressure, Opportunity, and Capability in the Public Sector - Anita Nursanti; Fitri Fitri (STIE Amkop Makassar, 2026)
The implementation of the Free Nutritious Meals (MBG) Program as a national strategic policy has created new challenges related to fraud risk in public-sector logistics and budget management. The large-scale implementation of the program, rapid financial transactions, and complex food supply chains may create opportunities for fraudulent practices. However, empirical studies examining the determinants of fraud risk in the context of the MBG Program remain limited. This study aims to empirically examine the effects of pressure, opportunity, and capability on fraud risk in the MBG Program in the KPPG Bogor area. A quantitative approach with a causal-comparative research design was employed using a survey method. The research population consisted of volunteers, administrative staff, and technical personnel directly involved in the implementation and distribution of the MBG Program in the KPPG Bogor area. Respondents were selected using purposive sampling based on predetermined inclusion criteria. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS. The results indicate that opportunity and capability have positive and significant effects on fraud risk, with capability demonstrating the strongest effect. In contrast, pressure does not have a significant effect on fraud risk. These findings indicate that fraud risk in the MBG Program is more strongly associated with the availability of opportunities and the capabilities of individuals to exploit weaknesses in the control system than with economic or performance-related pressure. The study highlights the importance of strengthening internal controls, access authorization, logistics monitoring, and technology-based reporting systems to mitigate fraud risk in the implementation of the MBG Program.